Determining Gibbs energies of adsorption from corrosion inhibition efficiencies: Is it a reliable approach?. (15th July 2019) - Walczak, Monika S.; Morales-Gil, Perla; Lindsay, Robert
Graphical abstract: Highlights: Question use of inhibition efficiency to obtain standard Gibbs energy of adsorption. Demonstrate that inhibition efficiency is not always equivalent to surface coverage. Probe validity of applying the Langmuir isotherm to a corrosion inhibitor system. Abstract: The common practice of using inhibition efficiency (η%) to determine the standard Gibbs energy of adsorption ( ΔG ads o ) for a corrosion inhibitor in acidic solution is evaluated. It is demonstrated that the typical assumption that η% is a good proxy for fractional surface coverage (θ) is not necessarily valid. Consequently, the accuracy of the ΔG ads o value obtained from such data is doubtful. Moreover, it is argued that even a more direct measurement of θ may still not allow one to extract an accurate estimate of ΔG ads o .